(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2023)
The text analyzes how the problem of the thing in itself in Kant (insofar it is a real foundation of the phenomenon) was considered by post-Kantian philosophers and how they sought to solve the possible dualism of critical philosophy. This investigation focuses mainly on Schopenhauer's response to such a problem, evidenced for the first time by the philosopher Friedrich Heinrich Jacobi, who was one of the great critics of transcendental philosophy and idealism.